A Substandard Autobiographical Sketch in Three Chapters. (July 2022) - Singh, Harshit Pratap
All aspects of our lives, including educational access and quality, are affected by our socio-economic position. This reflective note about the author's educational experiences describes the interlinkages of caste and education. It talks about how those experiences played an integral role in shaping the author's beliefs about caste, reservation and merit, and made him challenge the implicit as well as explicit forms of discrimination prevalent in our society. The autobiographical sketch is anchored around the idea of 'merit' and the perceived non-meritoriousness of students belonging to the reserved categories (especially SC and ST). These first-hand as well as second-hand experiences of caste-based discrimination paint a contextual and grounded picture of the challenges faced by the author (and other Dalit students) in his education. The note ends with an implicit demand for dignity and the need of acknowledging the struggles of students from marginalised communities by not isolating their experiences from the sociological context that they are part of.